The effects of anaemia and transfusion on patients with traumatic brain injury: A review. (5th December 2016) - Travers, Sarah; Martin, Simon; Litofsky, N. Scott
Abstract: Background : Anaemia in traumatic brain injury (TBI) is frequently encountered. Neurosurgical texts continue to recommend transfusion for hematocrit below 30%, despite clear evidence to do so. Transfusion should increase oxygen delivery to the brain, but it may also increase morbidity and mortality. Methods : This study reviewed the relevant literature to better understand the risks of anaemia and benefits of correction of anaemia by transfusion. Results : Of the 21 studies reviewed, eight found that anaemia was harmful to patients with TBI; five found no significant outcome; seven found transfusion was associated with higher rates of morbidity and mortality; two found that transfusion lowered mortality and increased brain tissue oxygen levels; and ten found no correlation between transfusion and outcome. However, the levels of anaemia severity and the outcome measurements varied widely and the majority of outcomes focused on crude measurements rather than detailed functional assessments. Conclusions : No division of response based on gender difference or impact of anaemia in the post-hospital treatment setting was observed. A randomized control trial is recommended to determine the impact of anaemia and transfusion on detailed outcome assessment in comparison of transfusion thresholds ranging from ≤ 7 g dL –1 to ≤ 9 g dL –1 in patients with moderate-to-severe TBI.